The efficiency of some plant extracts for growth inhibition of Candida albicans and Trichophytonmentagrophytes (Baghdad Science Journal, 2025)
Plant extracts occupied a big place in diseases treatment and preserving human health because, they contain many active substances that can be exploited in the field of pharmaceutical manufacturing from natural materials. Therefore, this study was conducted to evaluate the effect of different concentrations of plant extracts for each of Nigella sativa, Alliumsativum and Allium cepa against the fungal growth of Candida albicans that cause many skin diseases and infections to humans as well as Trichophyton mentagrophytes, which affects the hair, skin and nails.These two fungi have been isolated and diagnosed from people who have skin infection. Both fungal isolates were treated with extracts of Nigella sativa, Alliumsativum and Allium cepa, which are prepared by using the cold method of extraction.The results showed the effectiveness of Nigella sativa extract against C. albicans and T. Mentagrophytes within two weeks of incubation period. On the other hand, it has been found that the extract of Nigella sativa was more effective on C. albicans, as the rate of inhibition zone was 3.0-4.2 in diameter and 4.5-5.0 on SDA and ESDA media respectively. The results of the fungus T. mentagrophytes indicated that the inhibition zone was 3.2 -3 cm in diameter on SDA medium and 3.0- 4.2 cm on ESDA medium compared with control, as there were no inhibition zones appearance for both fungi. Moreover, the results showed that Allium sativum extract comes in second place in their effectiveness against fangal growth, whereas, the Allium cepa extract did not show any significant impact